Use of Sediment Geochemistry and Video Analysis for habitat description of the sea cucumber Holothuria (Roweothuria) poli - CHATZIVASILEIOU, DIMITRA; PANANGANAN, BERNADETH GRACE S.; DIMITRIOU, PANAGIOTIS D.; PAPAGEORGIOU, NAFSIKA; LAMPA, MARIA; MANOLAKI, STEFANIA; YU, ZHENGLIN; HUO, DA; YUAN, XIUTANG; KARAKASSIS, IOANNIS (Mediterranean Marine Science, 2026)
The increasing commercial value of holothurians has triggered considerable scientific interest. The aim of the study was to investigate Holothuria (Roweothuria) poli populations and sediment characteristics in two contrasting coastal areas in the same geographic region. The first (S1) consists of an exposed sandy, low organic material and well-oxygenated seabed. The other (S2) is sheltered, with a silty sediment, high labile organic matter, and negative redox values. H. poli populations were studied monthly by means of ROV survey while sediment samples were collected seasonally. At S2, holothurians were significantly more abundant and with higher biomass. In both areas, seasonal patterns were observed, with S1 presenting a peak of density and biomass during the summer months, while in S2 the peak was recorded in spring. The H. poli distribution seemed to be determined by environmental and biological factors, including availability of food resources, redox regime in the sediments and spawning-related behaviour.